2017
DOI: 10.1111/fme.12210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of observer‐ and industry‐based catch data in a recreational charter fishery

Abstract: There is international recognition for greater inclusion of recreational fisheries catch data in species, fisheries and ecosystem assessments. Recreational charter fisheries provide important social services and contribute to total species catches. This study compares and validates industry logbook catch and effort data (1,357 trips) against observer data (154 trips) across six ports in a recreational charter fishery in eastern Australia. The mean numbers of clients and fishing effort (hours) per trip varied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Lewin, Arlinghaus & Mehner, ; West et al., ; Wise, Telfer, Lai, Hall & Jackson, ). This study, along with that reported in Gray and Kennelly (), demonstrates how observer‐based sampling can provide independent catch (retained and discarded), effort and demographic data on key species in a recreational fishery. The ongoing collection of such data could contribute to species, fisheries and ecosystem assessments and ultimately the management of resilient and sustainable recreational charter fisheries.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Lewin, Arlinghaus & Mehner, ; West et al., ; Wise, Telfer, Lai, Hall & Jackson, ). This study, along with that reported in Gray and Kennelly (), demonstrates how observer‐based sampling can provide independent catch (retained and discarded), effort and demographic data on key species in a recreational fishery. The ongoing collection of such data could contribute to species, fisheries and ecosystem assessments and ultimately the management of resilient and sustainable recreational charter fisheries.…”
Section: Discussionsupporting
confidence: 66%
“…Fletcher, ; Hobday et al., ). This study and that reported in Gray and Kennelly () have provided important insights into designing and implementing any ongoing programs to independently monitor, evaluate and report on, charter fisheries and stocks of recreational fish species.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…). In many cases, modes of capture are relatively indiscriminate, with fishing gears such as hook and line and nets capturing a wide range of species in the same location (Gray and Kennelly ; Northridge et al. ).…”
mentioning
confidence: 99%
“…Fisheries are often a complex blend of motivations and human-fish interactions (Cooke and Cowx 2006;Young et al, 2016). In many cases, modes of capture are relatively indiscriminate, with fishing gears such as hook-and-line and nets, being able to capture a wide range of species in the same location (Gray and Kennelly, 2017;Northridge et al, 2017). Many fish are released to comply with harvest restrictions, or as a voluntary behaviour on behalf of the fisher for conservation purposes or because the bycatch is considered low value to the fisher (Arlinghaus et al, 2007;Davies et al, 2009).…”
Section: Introductionmentioning
confidence: 99%